Analisis Kebutuhan Pengembangan E-Modul Flipbook Interaktif Berbasis Game Based Learning (GBL) Pada Materi Sistem Pernapasan Kelas VIII Smp - Siti Nurhalizah; Sepita Ferazona; Nurkhairo Hidayati (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Science learning on the respiratory system material for grade VIII junior high school is still dominated by lecture methods and the use of conventional media, so that students' activeness and visual understanding have not developed optimally. This study aims to analyze the needs of teachers and students for the development of interactive flipbook E-Module teaching materials based on Game Based Learning (GBL) on the respiratory system material for grade VIII junior high school. The study used a quantitative descriptive approach with subjects of one science teacher and 29 grade VIII students of UPT SMP Negeri 1 Siak Hulu. Data were collected through teacher interviews and student needs analysis questionnaires covering four indicators, namely learning approaches/methods, learning media, teaching materials, and assessments. Data were analyzed using percentage techniques. The results of the analysis showed that all indicators were in the very needed category, with the percentage of learning approaches/methods of 82.76%, learning media 79.83%, teaching materials 81.38%, and assessment 85.17%. The interview results also showed that students were more active when learning involved game elements. Thus, interactive digital learning media is needed that suits the needs of teachers and students as a basis for developing more interesting and effective science learning.